Brother Odd / a novel - Koontz, Dean R. frey50; Baker, David Aaron, 1963- (New York : Random House Audio, 2006)
St. Bartholomew's Abbey sits in majestic solitude amid the wild peaks of California's high Sierra, a haven for children otherwise abandoned, and a sanctuary for those seeking insight. Odd Thomas has come here to learn to live fully again. But trouble has a way of finding Odd Thomas, and it slinks back onto his path.
Unabridged.
Compact discs.
Read by David Aaron Baker.
Keywords: Mediums; Missing persons